2011
DOI: 10.1111/j.1365-2966.2011.19748.x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical state of stellar structure in star-forming regions

Abstract: The fraction of star formation that results in bound star clusters is influenced by the density spectrum in which stars are formed and by the response of the stellar structure to gas expulsion. We analyse hydrodynamical simulations of turbulent fragmentation in star-forming regions to assess the dynamical properties of the resulting population of stars and (sub)clusters. Stellar subclusters are identified using a minimum spanning tree algorithm. When considering only the gravitational potential of the stars an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
209
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(220 citation statements)
references
References 62 publications
(111 reference statements)
11
209
0
Order By: Relevance
“…Recent observations did not find the expansion velocities that are expected if gas expulsion was important (e.g., Hénault-Brunet et al 2012). Hence, the dispersal is probably related to tidal effects (e.g., Kruijssen et al 2012a) that could take as long as 200 Myr (Kruijssen et al 2012b). It is therefore reasonable to assume that for the timescales of interest here, the great majority of massive stars are grouped (compare also Zinnecker & Yorke 2007).…”
Section: Which Star Clusters Produce How Much 26 Al?mentioning
confidence: 84%
“…Recent observations did not find the expansion velocities that are expected if gas expulsion was important (e.g., Hénault-Brunet et al 2012). Hence, the dispersal is probably related to tidal effects (e.g., Kruijssen et al 2012a) that could take as long as 200 Myr (Kruijssen et al 2012b). It is therefore reasonable to assume that for the timescales of interest here, the great majority of massive stars are grouped (compare also Zinnecker & Yorke 2007).…”
Section: Which Star Clusters Produce How Much 26 Al?mentioning
confidence: 84%
“…2.2 do not assume any primordial gas present initially in the cluster, i.e., the cluster is taken to be formed with 100% local SFE. A high local SFE has been claimed by several authors based on hydrodynamic calculations without or partially-implemented feedback processes (e.g., Klessen et al 1998;Bate & Bonnell 2004;Kruijssen et al 2012;Girichidis et al 2012;Dale et al 2015). Clearly, as the computations in Sec.…”
Section: Non-secular Evolution Of Star Clusters: Primordial Gas Expulmentioning
confidence: 99%
“…From such observations, it can be generally concluded that the individual filamentary overdensities and their junctions in molecular clouds are highly compact; of typical (projected) widths of 0.1-0.3 pc (André et al 2011. Both theoretical and observational studies indicate that groups of (proto-)stars preferentially form within the filaments and at filament junctions Schneider et al 2010Schneider et al , 2012Tafalla & Hacar 2014;Duarte-Cabral et al 2011), giving rise to 0.5 pc dense protostellar clumps (or pre-cluster cloud core; e.g., Lada & Lada 2003;Tapia et al 2011;Traficante et al 2015). Semi-analytic studies, e.g., Marks & Kroupa (2012), also indicate similar gas clump sizes that depend weakly on their total mass.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations